Impacts of Mesoscale Currents on the Diurnal Critical Latitude Dependence of Internal Tides: A Numerical Experiment Based on Barcoo Seamount. Issue 4 (5th April 2019) - Dong, Jihai; Robertson, Robin; Dong, Changming; Hartlipp, Paul Scott; Zhou, Tianyu; Shao, Zhibo; Lin, Weihong; Zhou, Muzhi; Chen, Jiarui
Abstract: Critical latitudes are a significant area of tidal dissipation. Generally, critical latitudes are taken to be the exact latitude where the tidal frequency equals the inertial frequency. However, the key is really where the tidal frequency equals the combination of planetary vorticity and relative vorticity from background currents. Although the influence of background currents on critical latitude effects and nonlinear interactions have been noted for many years, their exact impacts are not well known. The latitude dependence of critical latitude impacts on the tides, internal tides, and internal waves in the presence of background currents was investigated using the Regional Ocean Modeling System by shifting a small domain including a seamount from 20.6° to 38.6°S and comparing simulations with and without background currents. The diurnal kinetic energy with mesoscale currents was relatively unchanged for most latitudes, except for a slight decrease 1–4° poleward of the critical latitude. However, the semidiurnal and high‐frequency (≥3 cycles per day) kinetic energy increased with the presence of mesoscale currents, especially within the diurnal critical latitude range. Spectral and nonlinear analyses indicated mesoscale currents broadened the range of critical latitude effects and enhanced energy transferring from diurnal frequencies to semidiurnal and high frequencies and from low to high mode waves. Local diffusivities increased, roughly an order of magnitude, when mesoscale currents were present. The impacts of mesoscale currents on the broadening of the critical latitude range and enhancement of nonlinear interactions were attributed to the additional relative vorticity and near‐inertial internal waves generated by mesoscale currents. Plain Language Summary: Resonant effects become important with tides near the latitude where the natural inertial frequency based on the Coriolis factor equals the tidal frequency. The latitude where the tidal frequency equals the natural inertial frequency is called the critical latitude, and for the diurnal tides, it occurs at 27.6° and 30° latitude, both North and South. Commonly, the critical latitude is perceived as an exact latitude. However, background currents can shift the exact latitude where this occurs. In this study, the latitude dependence of the internal tidal response and mixing were investigated with a realistic background current present. Since background currents are nearly ubiquitous in the ocean, this is a very realistic situation. The presence of background currents was found to enhance the internal tidal generation and mixing and to broaden the range of latitudes impacted by resonant interactions associated with the critical latitude. These factors were attributed to a modification of the relationships for the tide resulting from the additional relative vorticity and near‐inertial internal waves from the background currents. Key Points: Energy at semidiurnal and harmonic frequencies was enhanced when mesoscale currents interacted with internal tides Nonlinear interactions were enhanced at the critical latitude, and the latitude range affected was broadened with mesoscale currents presence Vertical diffusivities increased by an order of magnitude when mesoscale currents interacted with internal tides